Vidkrytyj tei͏̈zm: krytyčnyj analiz = Open Theism: A Critical Analysis - Kartajev, Volodymyr (Bogoslovs'ki rozdymi, 2021)
Kartaiev, Volodymyr. "Open Theism: A Critical Analysis." The dissertation for the degree of candidate of philosophical sciences- 09.00.14 (041 - Theology). This dissertation provides a critical analysis of the methodological, philosophical, andhermeneutic aspects of open theism as a conceptual model of providence. Open theism is a revision of the classical model of God’s providence. It has been proven that despite significant modification, open theism can be called part of the theological family of Arminianism. At the same time, fundamental disagreements prevent the identification of open theism with process theology. It is shown that open theism is in essence a God-centered model. Divine life is social life. Open theism tries to correct, and if necessary, eliminate all elements of the providence model that contradicts love. It was discovered that of the three versions of open theism, only one falls within the confines of Christian orthodoxy. This is a version that denies the existence of the truth about future events (alethic openness) on the basis of causal, providential, and ontic openness of the future.